Herbal Cigarette Sales Information System Case Study at Stockis Sin Sriwijaya - Salma Saepul Milah; Rival Khafi Fergian; Sony Chandra Maulana; Jajat Sudrajat; Heri Wahyudi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
There is still space for improvement in the application and usage of technology and information in the sales business, as indicated by the significant percentage of clients who continue to make manual purchases. An example would be the present Sriwijaya Herbal Sin Cigarettes retailer. The Sin Cigarette Herbal Sriwijaya stockist shop employs a traditional sales system where consumers physically visit the shop to make purchases. This research aims to enhance consumer convenience by developing a sales information system for herbal cigarettes, enabling online access to sales. This study employs a descriptive research methodology and a waterfall system development approach. This approach involves sequential steps, including needs analysis, design, code production, testing, and support. Data collection from the users was followed by the design and development stage of the program, employing the PHP programming language for implementation. Subsequently, an evaluation was conducted on the functioning system. The outcome is a sales information system that is anticipated to possess the capability to process data into high-quality information efficiently, seamlessly integrate various components, and serve as a repository for data storage. With the existence of this sales information system for herbal cigarettes, the processing of sales data has been computerized automatically, enabling automated report generation. This study introduces an internet-based sales information system for the Sriwijaya Herbal Cigarette Stockist Shop. It replaces traditional sales procedures, expands market reach, streamlines report generation, provides comprehensive buyer information, and maximizes profitability. The innovation employs the waterfall system development methodology and the PHP programming language to enhance retail operations' effectiveness and efficiency. An inherent constraint of this study is the need for the online-based sales information system to address all challenges the Sriwijaya Herbal Cigarette Stockist Shop faces, including technological infrastructure and user proficiency issues. Reliable internet connectivity is crucial for the system's effectiveness, which may require improvements in certain regions. Additionally, employees and customers may require additional training to use the new systems proficiently, which should be considered in terms of time and resources for this research.